Tolerance to chronic neuromuscular fatigue during a training microcycle in a European rugby team - Albesa-Albiol, L.; González-Millán, S.; Caparrós, T.; Piedra, A.; Pardo, P.; Guerrero, S. (Apunts Sports Medicine, 2026)
The aim of this study was to analyze the chronic neuromuscular fatigue over the course of training microcycle (one week) in 27 rugby players, differentiating between professional (n = 10) and non-professional (n = 17) athletes from the same team, as well as considering training load distribution and playing positions. A retrospective observational study was conducted, in which participants performed countermovement jumps (CMJ) before and after training sessions using a Chronojump Boscosystem contact platform. A total of 464 jumps were analyzed (234 pre- and 230 post-training), recording metrics such as jump height, flight time, average propulsive power, and initial velocity. Professional players showed higher values in jump height (39.36± 4.24 cm), average power (1348.34±149,72 W) as well as a better reactive strength index (0.57), compared to non-professionals, who exhibited accumulated reductions in jump height (35,32± 6.80 cm), power (1176,62±26,96 W), and initial velocity (2,65±0,26 m/s) throughout the microcycle, indicating greater neuromuscular fatigue. Regarding playing positions, front-row players demonstrated lower average jump height (34.95±7,97 cm), while backline players stood out for higher speed (2.823±0,15 m/s) and power for back row (1381.92±171,87 W).A positive effect of gym-based activation exercises prior to field training was observed, associated with improvements in jump height (38.62±6,07 cm vs. 36.31±6,05 cm; F = 14.8; p < 0.01; SE=0.03) power (1298.48±203,3 W vs. 1231.26±166,47 W), and initial velocity (2.75±025 m/s vs. 2.66±0,22 m/s). suggesting a post-activation potentiation (PAP) effect that could temporarily enhance neuromuscular performance. Therefore, incorporating PAP protocols before field sessions may be an effective strategy to optimize athletes' physical performance.